Deficiency in alcohol dehydrogenase 2 reduces arsenic in rice grains by suppressing silicate transporters. Issue 1 (22nd February 2021) - Hayashi, Shimpei; Kuramata, Masato; Abe, Tadashi; Yamaguchi, Noriko; Takagi, Hiroki; Tanikawa, Hachidai; Iino, Manaka; Sugimoto, Kazuhiko; Ishikawa, Satoru
Abstract: Paddy fields are anaerobic and facilitate arsenite (As(III)) elution from the soil. Paddy-field rice accumulates arsenic (As) in its grains because silicate transporters actively assimilate As(III) during the reproductive stage. Reducing the As level in rice grains is an important challenge for agriculture. Using a forward genetic approach, we isolated a rice ( Oryza sativa ) mutant, low arsenic line 3 ( las3 ), whose As levels were decreased in aerial tissues, including grains. The low-As phenotype was not observed in young plants before heading (emergence of the panicle). Genetic analyses revealed that a deficiency in alcohol dehydrogenase (ADH) 2 by mutation is responsible for the phenotype. Among the three rice ADH paralogues, ADH2 was the most efficiently produced in root tissue under anaerobic conditions. In wild-type (WT), silicon and As concentrations in aerial tissues increased with growth. However, the increase was suppressed in las3 during the reproductive stage. Accordingly, the gene expression of two silicate transporters, Lsi1 and Lsi2, was increased in WT around the time of heading, whereas the increase was suppressed in las3 . These results indicate that the low-As phenotype in las3 is due to silicate transporter suppression. Measurement of intracellular pH by 31 P-nuclear magnetic resonance revealed intracellular acidification of las3 roots under hypoxia, suggesting that silicate transporter suppression in las3 might arise from an intracellular pH decrease, which is known to be facilitated by a deficiency in ADH activity under anaerobic conditions. This study provides valuable insight into reducing As levels in rice grains. Abstract : Deficiency in alcohol dehydrogenase suppresses arsenite uptake via silicate transporters and reduces arsenic levels in rice grains.